Dampak Program PUAP terhadap Pendapatan Petani Beras di Kabupaten Kupang, Provinsi Nusa Tenggara Timur - Umbu Joka; Lukytawati Anggraeni; Anna Fariyanti (Fakultas Pertanian, Universitas Timor, 2019)
Rural Agribusiness Development Program (PUAP) is a breakthrough program from Ministry of Agriculture for poverty reduction and job creation, while reducing the development gap between regions and regional centers and sub-sectors. The purpose of this study is on the impact of the PUAP program on analyze the income of rice farmers direct benefit recipients community (BLM) PUAP. The PUAP Program impact on Farmers income were analyzed using t-test, farm income analysis and linear regression model. The analysis showed PUAP program significantly affect farmer’s income.